Dampak Adopsi QRIS Pada UMKM Sektor Food and Beverage Di Banda Aceh - Nanda, Teuku Syifa Fadrizha; Evriyenni; Rahmi (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Advances in information technology have driven transformations in payment systems, and the COVID-19 pandemic serves as a catalyst for the financial services industry worldwide to accelerate shifts in payment systems toward cashless payment systems. Ironically, a preliminary study conducted among MSMEs in the food and beverage (F&B) sector in Banda Aceh indicated that utilization of QRIS is considerably low, with only 20% indicating that the intensity of customer transactions through QRIS is rated medium to high and 80% indicating low intensity. This phenomenon drove this study to investigate the impact and challenges associated with utilizing QRIS as an alternative payment system in the F&B industry in Banda Aceh. We investigated this issue employing a descriptive qualitative approach, and data was collected on MSME owners in the designated industry in Banda Aceh by performing observation, interviews, and documentation. Afterwards, the collected data were analyzed using Nvivo 12. According to the findings of this study, adopting QRIS in the payment system increases the ease of transaction, business operational efficiency, and rapid access to transaction data. However, the adoption of QRIS among MSMEs in (F&B) industry in Banda Aceh is relatively low. Some challenges in adopting QRIS have lagged interconnectivity between payment aggregators, disrupting the transaction process and delaying customer transaction payments. During hectic seasons such as weekends, national holidays, and religious holiday, the intensity of these technical obstacles frequently increases. Aside from that, public awareness and acceptance of electronic payment transactions remain low due to city dwellers’ lack of digital financial literacy.